Ionomic, metabolomic and proteomic analyses reveal molecular mechanisms of root adaption to salt stress in Tibetan wild barley - Shen, Qiufang (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.